2021
DOI: 10.1002/ppul.25625
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human milk and other neonatal variables on lung function at three months corrected age

Abstract: Objective: To evaluate the impact of human milk and different neonatal variables on tidal breathing flow-volume loop (TBFVL) parameters within three months' corrected age (CA) in infants born ≤32 wks or weighing <1500 g. Methods:We retrospectively studied 121 infants with gestational age (GA) ≤ 32 weeks or birth weight (BW) <1500 gr who had lung function assessment within three months'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…To explore the association between maternal PA level in the first half of pregnancy and infant lung function we have only adjusted for variables potentially affecting both the exposure and the outcome. Thus, neither pregnancy complications nor infant factors such as sex, GA, birth weight or breastfeeding [ 6 , 8 , 23 , 27 , 30 , 40 ], previously shown to affect lung function, were regarded as potential confounders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the association between maternal PA level in the first half of pregnancy and infant lung function we have only adjusted for variables potentially affecting both the exposure and the outcome. Thus, neither pregnancy complications nor infant factors such as sex, GA, birth weight or breastfeeding [ 6 , 8 , 23 , 27 , 30 , 40 ], previously shown to affect lung function, were regarded as potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Tidal volume ( V T ) increases after birth [ 28 , 29 ], with lower volumes in early infancy observed with prematurity [ 30 ] and lung hypoplasia [ 31 ]. While most studies exploring lung function in infancy have been performed in sleeping or sedated infants, both t PTEF / t E and V T seem to be higher in the awake compared to the sleeping state [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study provides additional evidence for a synergistic adverse effect of prenatal exposure to ETS and advanced paternal age on the lung function in offspring. Several studies have shown that breastfeeding could improve lung function in children [26][27][28]. Our study suggests that breast milk may more effectively promote the programming of the children's developing respiratory system than infant formula and counteract the harmful effect of advanced paternal age.…”
Section: Resultsmentioning
confidence: 61%
“…The adjusted covariates were listed as follows: child's age, sex, height, maternal age at birth, prematurity (gestational age less than 37 weeks), birth weight, cesarean delivery, birth order, physician-diagnosed asthma, parental university education, parental allergic diseases (physiciandiagnosed asthma, allergic rhinitis or atopic dermatitis in mother, father or both), prenatal exposure to ETS (one or more household smokers during gestation), breastfeeding (exclusive or partial) longer than 6 months, and household income, which were similar to previous relevant studies [12,14,17,23]. We performed subgroup analysis, stratified by prenatal exposure to ETS and breastfeeding which were associated with lung function and FeNO in previous studies [24][25][26][27][28][29], to evaluate potential effect modifiers. Sensitivity analyses were performed by converting lung function parameters to z-scores based on the GLI-2012 reference equations.…”
Section: Discussionmentioning
confidence: 77%
“…These findings are in line with previous literature, showing that formula‐fed preterm infants carry a higher risk of compromised lung function. An eloquent example of this is the trial recently published in Pediatric Pulmonology by Beretta et al, 4 in which the role of prevalent human milk feeding for limiting expiratory obstruction in infants with birth weight <1000 g was shown. Regarding the influence of type of human milk feeding on respiratory support duration, Sun et al 5 had found that infants whose mothers were asked to provide at least one feed of fresh milk per day from the time of enrollment, spent fewer days on mechanical ventilation and fewer days on parenteral nutrition than the control group, that included mothers who did not agree to provide fresh milk, but agreed for their infants to receive exclusively donor or frozen mother's own milk.…”
mentioning
confidence: 99%